Museums, memories and social movements (Cadernos de Sociomuseologia, 2010)
From modernity to the contemporary world, museums have been acknowledged for their power to produce metamorphoses of meanings and functions, for their ability to adapt historic and social determination, and for their calling for cultural mediation. They derive from creating gestures which bind the symbolic and the material, which bind what is sensitive and what is intelligible. For this very reason the bridge metaphor fits them well, a bridge cast between different times, spaces, individuals, social groups and cultures, a bridge that is built with images and which holds a special place in the imaginary.